2022
DOI: 10.18176/jiaci.0710
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis to Sunflower Seed With Tolerance to Other Nuts: The Role of Lipophilic Allergens

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…3 Others case reports of anaphylactic reactions to sunflower seed have been published. 1,[6][7][8][9][10][11][12][13][14][15][16][17][18][19] Garcia Ortiz et al 10 reported 15 reactions to sunflower seed ranging from OAS to anaphylaxis in a series of 84 patients monosensitized to Artemisia pollen. Comparing to our series, they found a lower proportion of severe reactions, only 2/15 (13%) of the patients reporting anaphylaxis after sunflower seed ingestion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Others case reports of anaphylactic reactions to sunflower seed have been published. 1,[6][7][8][9][10][11][12][13][14][15][16][17][18][19] Garcia Ortiz et al 10 reported 15 reactions to sunflower seed ranging from OAS to anaphylaxis in a series of 84 patients monosensitized to Artemisia pollen. Comparing to our series, they found a lower proportion of severe reactions, only 2/15 (13%) of the patients reporting anaphylaxis after sunflower seed ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…Despite frequent consumption, since first sunflower seed allergy reported by Noyes et al 1 in 1979, publications on sunflower seed allergy have been limited to case reports or case series with small number of patients. 1,[6][7][8][9][10][11][12][13][14][15][16][17][18][19] This study was conducted to evaluate the clinical and immunological features of IgE-mediated hypersensitivity to sunflower seed as well as other food allergies present in sunflower seed allergic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Other case reports of anaphylactic reactions to sunflower seed have been previously published. 1,[8][9][10][11][12][13][14][15][16][17][18][19][20][21] Garcia Ortiz et al 12 reported 15 reactions to sunflower seed ranging from OAS (oral allergy syndrome) to anaphylaxis in 11 patients from a series of 84 patients monosensitized to Artemisia pollen. Compared to our series, they found a lower proportion of severe reactions, with only 2 anaphylaxis after sunflower seed ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…A review of four patients reacting to pumpkin seeds but not the pulp, identified two allergens, although only Cuc ma 5 (2S albumin) was positive in all four cases [54]. Sunflower seeds contain both 2S Albumins and nonspecific Lipid Transfer Protein (nsLTP) allergens, but a lipoprotein such as an oleosin could also be responsible for severe reactions, especially to roasted seeds and in the absence of sensitisation or reactions to other foods [55,56]. A recent review by Majsiak and colleagues suggests oleosins could also be responsible for reactions to sunflower seeds when allergy tests were negative [57].…”
Section: Seedsmentioning
confidence: 99%